1989
DOI: 10.1007/bf00043400
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing shoot regeneration from cotyledonary explants ofCucumis melo

Abstract: Cotyledonary explants of 4-day-old Cucumis melo cv. 'Hale's Best Jumbo' in vitro seedlings showed maximum initiation of shoot buds when cultured onto a revised Murashige & Skoog medium supplemented with 5/~M indole-3-acetic acid and 5/~M benzylaminopurine and cultured at 25-29°C under low light intensity (5-30#molm-2s-~). Subculture of the shoot buds onto the same medium without auxin and supplemented with 3 #M benzylaminopurine caused the development of shoots from 30% of the buds. The presence of abscisic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 7 publications
3
23
2
3
Order By: Relevance
“…Several protocols for melon have been described using different explants such as hypocotyls, cotyledons, leaves and roots (Moreno et al, 1985;Trulson and Shahin, 1986;Niedz et al, 1989;Bordas et al, 1991;Tabei et al, 1991;Souza, 1999;Souza, 2001;Lotfi et al, 2003). The results have shown that protocols using leaf explants were less efficient.…”
Section: Resultsmentioning
confidence: 99%
“…Several protocols for melon have been described using different explants such as hypocotyls, cotyledons, leaves and roots (Moreno et al, 1985;Trulson and Shahin, 1986;Niedz et al, 1989;Bordas et al, 1991;Tabei et al, 1991;Souza, 1999;Souza, 2001;Lotfi et al, 2003). The results have shown that protocols using leaf explants were less efficient.…”
Section: Resultsmentioning
confidence: 99%
“…Although differences in regeneration capacity among cultivars of melon have been reported (Blackman and Reynolds, 1982;Bouabdallah and Branchard, 1986;Dirks and van Buggenum, 1989;Mackay et al, 1988;Niedz et al, 1989;Orts et al, 1987) variation among plants within the same population has not been studied nor have tests with the descendants been carried out. The results presented here showed sexual transmission of regeneration capacity from plants with high as well as low organogenic response to their offspring.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of genetic background on morphogenic responses has been previously demonstrated from quantitative genetic studies, from Mendelian genetic analysis and from gene mapping (Henry et al, 1994). Differences in morphogenic competence were found among melon cultivars and among plants of the same cultivar (Blackmon and Reynolds, 1982;Bouabdallah and Branchard, 1986;Gray et al, 1993;Niedz et al, 1989;Orts et al, 1987). In other horticultural crops, diallel crosses (Buiatti et al, 1974;Frankenbergeret al, 1981;Keyes et al, 1980;Kumar et al, 1985) and complete inheritance models (Hernandez and Christie, 1990;Kielly and Bowley, 1992;Koornneef et al, 1987;NadolskaOrczyk and Malepszy, 1989;Reisch and Bingham, 1980;Wan et al, 1988) have been used to study this phenomenon.…”
Section: Introductionmentioning
confidence: 91%
“…Niedz et a1. 19 reported that the frequency of shoot formation from cotyledon explants in melon was also reduced on 18-day-old seedlings when contrasted to explants from 4-day-old or 7-day-old seedlings. In a family of Cucurbitaceae, these facts suggest that cotyledons of mature seeds or young seedlings have high potential for shoot formation or somatic embryogenesis, and the potential of regeneration tends to disappear according to the aging of donor seedlings.…”
Section: Effect Of Preculturementioning
confidence: 99%